ANALISA SISTEM INFORMASI AKUNTANSI PENGGAJIAN UNTUK MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERNAL PADA PT GAMMA UTAMA SEJATI - Bella Natalia (2020)
This research a qualitative study using ethnomethodology methods and interpretive paradigms aimed at analyzing information systems in accounting on the payroll systems that have been used by PT Gamma Utama Sejati and analyzing information systems in the accounting in the payroll system on the effectiveness of internal control. The methods used in this study are observation, interview and documentation. The results in the study are (1) with the application of the accounting system of payroll information can increase the effectiveness of internal controls in PT Gamma Utama Sejati (2) a development in the use of functions and documents in support of the use of the payroll system